Jakub Chavalka – Ondřej Sikora (eds.): Nietzsche On Virtue: 2nd Special Issue of The Philosophical Journal, 2018. Prague, Filosofia 2018. 204 p. - Sajvera, David (Lidé města, 2019)
A review of the book by Jakub Chavalka and Ondřej Sikora.